Pressure support ventilation with the I-gel in intensive care unit: case report - Akan,Belgin (2016)
ABSTRACT BACKGROUND AND OBJECTIVES: The I-gel supraglottic airway has a non-inflatable cuff made from a gel-like thermoplastic elastomer. The use of the I-gel during anesthesia for spontaneously breathing patients or intermittent positive pressure ventilation has been reported. But there are a few published reports about the use of the I-gel with pressure-controlled ventilation. CONTENTS AND CONCLUSIONS: In this case report we described the use of the I-gel supraglottic airway along 48 h in intensive care unit for the management of ventilation in a patient needed mechanic ventilation but in whom tracheal intubation could not be performed.